Medizinbibliothekarische Bibliographie 2005 / The Medical Librarian's Bibliography 2005 - Bauer, Bruno (GMS Medizin – Bibliothek – Information, 2006)
The Medical Librarian’s Bibliography 2005 lists all articles from medizin - bibliothek - information and selected publications relevant to medical librarians from following journals: ABI Technik, Bibliothek Forschung & Praxis, Bibliotheksdienst, BIT online, Journal of the European Association for Health Information and Libraries, Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare, nfd, Online Mitteilungen, Zeitschrift für Bibliothekswesen & Bibliographie.